2017
DOI: 10.1038/s41598-017-08721-4
|View full text |Cite
|
Sign up to set email alerts
|

Emotions alter muscle proprioceptive coding of movements in humans

Abstract: Emotions can evoke strong reactions that have profound influences, from gross changes in our internal environment to small fluctuations in facial muscles, and reveal our feelings overtly. Muscles contain proprioceptive afferents, informing us about our movements and regulating motor activities. Their firing reflects changes in muscle length, yet their sensitivity can be modified by the fusimotor system, as found in animals. In humans, the sensitivity of muscle afferents is modulated by cognitive processes, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 64 publications
3
32
0
1
Order By: Relevance
“…There is now mounting evidence from human studies indicating that both muscle spindle static and dynamic sensitivity can be altered. Ackerley et al (2017) recently used microneurographic recordings of human ankle dorsiflexor muscle spindle Ia afferent activity to demonstrate increases in spindle dynamic sensitivity with unpleasant emotional state (sad music). Similarly, microneurographic recordings have been used to J Physiol 596.21 demonstrate that both static and dynamic sensitivity can be increased when attending to changes in limb position or movement velocity (Hospod et al, 2007;Ribot-Ciscar et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is now mounting evidence from human studies indicating that both muscle spindle static and dynamic sensitivity can be altered. Ackerley et al (2017) recently used microneurographic recordings of human ankle dorsiflexor muscle spindle Ia afferent activity to demonstrate increases in spindle dynamic sensitivity with unpleasant emotional state (sad music). Similarly, microneurographic recordings have been used to J Physiol 596.21 demonstrate that both static and dynamic sensitivity can be increased when attending to changes in limb position or movement velocity (Hospod et al, 2007;Ribot-Ciscar et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A potential contributor to balance changes that occur with height-induced postural threat could be modulations in muscle spindle dynamic sensitivity. Ackerley et al (2017) reported that unpleasant emotional state may increase ankle dorsiflexor muscle spindle dynamic responses to sinusoidal stretch, suggesting that muscle spindle sensitivity can be tuned to emotional context. Further evidence from postural threat studies has shown altered monosynaptic stretch reflexes with threats to standing balance.…”
Section: Introductionmentioning
confidence: 99%
“…The participant's emotional state was modified by listening to classical music through headphones (Bose; Framingham, MA). The music pieces had been previously defined as reliably inducing sad (n = 9 pieces), happy (n = 7), or neutral (n = 5) affective states (see [9] for details regarding the music pieces). Before the experiment started, the participant listened to the pieces of music and rated each of them on a visual analog scale (VAS), ranging from sad (equating to 0, the saddest they could feel) to happy (equating to 10, the happiest they could feel).…”
Section: Manipulation Of Emotional Statementioning
confidence: 99%
“…the gamma fusimotor system, making the receptors more or less responsive to changes in muscle length [7,8]. Recently, we demonstrated that the encoding of body movements by muscle spindles depends on the emotional context, by altering the top down control of muscle spindle sensitivity [9]. These results were obtained via microneurography, a technique which allows the recording of axonal unitary activity in sensory fibers in superficial nerves in humans [10].…”
Section: Introductionmentioning
confidence: 97%
“…Although sonification has demonstrated efficiency for motor rehabilitation, using music in sonification could improve the motivational component for such movement guidance . Emotional features of music can be observed even at the physiological level by modulating muscular afferences …”
Section: Introductionmentioning
confidence: 99%